Efforts of Kokoon Hotel Banyuwangi to Retain Potential Employees - Amanda, Amanda; Octafian, Ray (PT. Banjarese Pacific Indonesia, 2024)
The hospitality sector is one of the impacted industries, as it is closely connected to the tourism sector by providing lodging for tourists. However, there have been some favourable effects, such as the establishment of Kokoon Hotel Banyuwangi in reaction to the pandemic scenario. Increase in staff turnover is correlated with the appearance of opportunities that have resulted from the tourism recovery programme that the Indonesian government has implemented as a response to the Covid-19 outbreak, as was stated before. The research aims to investigate the employees' perception of the workplace climate at Kokoon Hotel Banyuwangi and determine the extent to which the work environment impacts their intention to continue working at the hotel. The qualitative method offers an opportunity for an in-depth exploration of Kokoon Hotel Banyuwangi's Efforts in Retaining Employees. This research found that skill development, career advancement, pay, work culture, benefits, and outstanding relationships affect employee satisfaction at Kokoon Hotel Banyuwangi. To retain staff, Kokoon Hotel Banyuwangi offers cross-training programmes, fair promotion processes, and a comfortable work culture for employee development. Kokoon Hotel Banyuwangi employees depart for financial, professional, and outside experience reasons. Kokoon Hotel Banyuwangi has to strengthen work culture, interactions with supervisors, coworkers, and subordinates, and employee skill development.